Proteomic profiling of serum in cats with naturally occurring degenerative joint disease and co-morbid conditions - Lascelles, B. Duncan X.; Ponnala, Rakesh; Kamerling, Steven G.; Williams, Tracey (Frontiers in Pain Research, 2025)
IntroductionDegenerative joint disease (DJD) occurs very commonly in cats and can be associated with pain. Almost 70% of cats with DJD-associated pain suffer the co-morbidity of chronic kidney disease (CKD). There are currently very limited treatment or management options. A greater understanding of the systems biology of DJD, DJD-associated pain, and CKD may contribute to identifying disease specific biomarkers and relevant targets for the development of therapeutics for the control of these conditions in cats, and help inform human pain therapeutic development.MethodsUsing mass spectrometry-based proteomic profiling of the serum of 200 highly phenotyped cats with varying burdens of DJD, pain, and CKD, we identified significant individual proteins and pathways.ResultsFunctional pathway analysis, based on differentially abundant proteins across individual disease states (DJD, pain, CKD), identified pathways playing a role in DJD and DJD-associated pain including acute phase response signaling, LXR/RXR and FXR/RXR activation and the complement system. With the added co-morbidity of CKD, similar pathways were identified, with the addition of IL-12 signaling and production in macrophages.DiscussionWe identified differentially abundant proteins associated with DJD, pain and CKD and future work should evaluate these proteins as potential biomarkers of disease (individually or as clusters). Further, these data could be leveraged to identify novel therapeutic targets to address the gap in our ability to manage DJD, pain, and CKD in cats. Given that our work was in cats with naturally occurring DJD, these results may have translational applicability to human health.